Characteristics Of Flavoring Mulberry Leaves And Shrimp Heads With Enzymatic Hydrolysis Using Papain And Calotropin - Amalia Rosida Fajriyah; Sri Winarti (UNIVED Press, Dehasen University Bengkulu, 2022)
Mulberry leaves are currently used as food for silkworms and livestock. Judging from the high protein content, it can be used as alternative flavoring. Mulberry leaves are combined with shrimp heads which high glutamic acid. Making flavoring is through a protein hydrolysis process using papain and calotropin enzymes. The purpose to determine the effect of concentration combination of papain and calotropin enzymes, as well as the hydrolysis time on flavoring characteristics. This study used a completely randomized design (CRD) two factors, enzyme combination concentration (1; 2; 3)% and hydrolysis time (1; 2; 3)hours. The best treatment was the flavoring with treatment enzyme combination concentration 3% and hydrolysis time 1 hour, with a characteristic hydrolysis degree 76.58%, dissolved protein 43.40%, water solubility index 0.087 gr/ml, oil absorption 1.20 ml/gr, water content 7.08% and flavoring yield 13.70% and organoleptic test results for taste 3.35 (slightly like), aroma 3.55 (slightly like), color 3.40 (slightly like) and overall 3.60 (somewhat like), and glutamic acid 783.07 mg/100g. Keywords: Calotropin; flavoring; mulberry leaves; papain; shrimp heads